Automatic online signature verification: A prototype using neural networks - Ahmed S.K.; Ramasamy A.K.; Khairuddin A.S.Mohd.; Omar J. (2023)
Signature verification is the process used to recognize an individual's handwritten signature to prevent fraud. In this paper pressure at the pen-tip together with the x, and y coordinates of the signature are measured and features extracted from these are used to verify the signature. A pressure pad was used to obtain signature samples. A signature verification system using SOM neural network was designed in MATLAB to verify the signatures. Results obtained using a prototype system are encouraging. The attractive features of this system are its low cost, low intrusion, good performance and use of an acceptable and natural biometric (the signature). 2009 IEEE.